2020
DOI: 10.1016/j.lwt.2020.109133
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of goat milk vacuum-assisted block freeze concentration using response surface methodology and NaCl addition influence

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Nevertheless, the concentration of total solids (CI = 4.00) achieved in the BFC test is considered high; this result and the low solids content verified in Ice 2 indicate that the BFC system is efficient for concentrating lactose‐free milk components. Machado Canella et al (2020) explained that this behavior is expected since the external driving force (vacuum) improves the natural division of gravitational thawing.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Nevertheless, the concentration of total solids (CI = 4.00) achieved in the BFC test is considered high; this result and the low solids content verified in Ice 2 indicate that the BFC system is efficient for concentrating lactose‐free milk components. Machado Canella et al (2020) explained that this behavior is expected since the external driving force (vacuum) improves the natural division of gravitational thawing.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, through a linear regression ( y = 0.8715 x − 0.3553, R 2 = 0.999), the °Brix results of the tests were converted and demonstrated as total solids content (g 100 g −1 ). Machado Canella et al (2020) applied this same correlation to semi‐skimmed goat milk ( y = 0.9285 x + 0.2764, R 2 = 0.999). In cases of readings of °Brix ≥4, the equation found by these authors shows similarity to our equation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, these studies are related to the efficiency and influence of freeze concentration in the biological activity (Adorno et al., 2017; Machado Canella et al, 2020; Orellana‐Palma et al., 2020) however, for agro‐industrial waste plant extracts concentration, few studies have been reported. Therefore, it is of great interest to use alternatives technologies that result in adding value to coproducts of agroindustry and, at the same time, sustainability.…”
Section: Introductionmentioning
confidence: 99%